Can Maternal Colostrum Be Replaced by Commercial Products for Feeding Newborn Calves? - Klibs N. Galvao (EDIS)
Colostrum management and feeding are critical for calf health, calves’ future productive life, and farm profitability. Current recommendations state that a calf needs to ingest at least 150–200 g of immunoglobulin G within two hours of birth, but when colostrum quality is poor or unavailable, colostrum replacer may be a suitable alternative. This 3-page fact sheet presents the results of a recent publication that evaluated the effects of feeding maternal colostrum, one dose of plasma-derived colostrum replacer, or one dose of colostrum-derived colostrum replacer on serum total protein, immunoglobulin G concentration, calf morbidity, calf mortality, and weight gain from birth to weaning. Written by Klibs N. Galvao and published by the UF Department of Veterinary Medicine-Large Animal Clinical Sciences, May 2014.